Research review: Post-earthquake fire assessment of steel buildings in the United States. Issue 1 (January 2018) - Chicchi, Rachel; Varma, Amit H
Researchers and practitioners have traditionally analyzed building hazards independently; however, with the recent focus on resilience, a multi-hazard analysis approach has emerged which considers the implications of cascading hazards. This article reviews the state of the art for analysis and design of steel moment frame buildings subjected to fires following earthquakes, also known as post-earthquake fires. The current design and analysis approaches for fire and seismic hazards in the United States, which follow prescriptive approaches, are each explained. Performance-based methodologies for each hazard are described. A literature review pertaining to the system behavior of buildings exposed to post-earthquake fires is provided. This includes consideration of nonstructural damage caused from earthquakes that could in turn affect building fire performance. Finally, recommendations are made for future post-earthquake fire analyses and design using incremental dynamic analyses and incremental fire analyses to capture building performance when subjected to various levels of these cascading hazards. The procedure for this methodology is explained, providing a direction for future research.